Adolescents with solid organ transplant: Using the BRIEF2 parent-report and self-report to measure parent-child agreement and everyday executive function. Issue 3 (3rd July 2022) - Hutchison, Sarah M.; Rathgeber, Steven L.; De Souza, Astrid M.; Blydt-Hansen, Tom; Mâsse, Louise C.; Armstrong, Kathryn R.; Oberlander, Tim F.
Abstract: Agreement between parent and adolescent ratings of executive function (EF) is not known in adolescents with solid organ transplant (SOT), even though pressing concerns about EF deficits are being raised in this population. The current study investigated EF in adolescents with SOT using parent and self report. Twenty-five adolescents ( M  = 15.51 years) with SOT and their parent completed a behavior rating scale assessing EF within everyday context using the Behavior Rating Inventory of Executive Function, Second Edition (BRIEF2). Parents and their adolescents demonstrated moderate to excellent agreement across the BRIEF2 clinical and index scores, higher than previous research with a typical sample. Adolescent males had higher agreement with their parents than female adolescents. Both parents and adolescents reported significantly higher mean T scores on various BRIEF2 indices and domains, in addition to higher rates of clinically elevated executive dysfunction than their peers. Assessment of EF and targeting specific EF domains for intervention may be useful in this population.